Facsimile Editions in O Castro, an Example of Recovering Historical Memory - Quintás Pérez, Leticia (Madrygal. Revista de Estudios Gallegos, 2015)
The publishing house Edicións do Castro was founded in 1963 with the aim of recovering Galicia’s historical memory, silenced during the years of the Franco regime. The present paper studies a part of the production of this publishing house, namely facsimile editions. It first focuses on their description and then carries out an analysis and subsequent evaluation of the relevance of these facsimile editions within the publishing scenario of the period.
Keywords: Historical memory; facsimile editions; Ediciós do Castro; Díaz Pardo; exile; repression